Cloning and characterization of the multisubstrate deoxyribonucleoside kinase of Drosophila melanogaster. - Johansson, M.; Van Rompay, A.R.; Degreve, B.; Balzarini, J.; Karlsson, A. (Journal of Biological Chemistry, 1999)
A Drosophila melanogaster deoxyribonucleoside kinase (Dm-dNK) was reported to phosphorylate all four natural deoxyribonucleosides as well as several nucleoside analogs (Munch-Petersen, B., Piskur, J., and Sondergaard, L. (1998) J. Biol. Chem. 273, 3926-3931). The broad substrate specificity of this enzyme together with a high catalytic rate makes it unique among the nucleoside kinases. We have in the present study cloned the Dm-dNK cDNA, expressed the 29-kDa protein in Escherichia coli, and characterized the recombinant enzyme for the phosphorylation of nucleosides and clinically important nucleoside analogs. The recombinant enzyme preferentially phosphorylated the pyrimidine nucleosides dThd, dCyd, and dUrd, but phosphorylation of the purine nucleosides dAdo and dGuo was also efficiently catalyzed. Dm-dNK is closely related to human and herpes simplex virus deoxyribonucleoside kinases. The highest level of sequence similarity was noted with human mitochondrial thymidine kinase 2, and these enzymes also share many substrates. The cDNA cloning and characterization of Dm-dNK will be the basis for studies on the use of this multisubstrate nucleoside kinase as a suicide gene in combined gene/chemotherapy of cancer.